Philosophy's Higher Education - Tubbs, Nigel; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
This book offers a re-reading of the philosophies of Kant, Hegel, Heidegger, Kierkegaard, Nietzsche and Rosenzweig. It argues that within the structure of their thinking lies a notion of the absolute which can be recognised as philosophy's higher education. This higher education is contained within and arises out of dualisms that are central to the work of each thinker: formation and finality (Kant), master and slave (Hegel), being and time (Heidegger), recollection and repetition (Kierkegaard), will to power and eternal return (Nietzsche), and fire and rays (Rosenzweig). The book argues that the dualisms have a speculative and therefore an educational significance which underpins the coherence of each thinker, and shows how, in each case, there subsists a notion of philosophy's higher education. The result of this investigation, therefore, is not only a radical re-interpretation of these philosophers, but also an ambitious attempt at unifying their work around another dualism, the relation of philosophy and education. It is within this latter relation that the book argues that the absolute can be realised.
Kant: Formation and Finality -- Hegel: Master and Slave -- Heidegger: Being and Time -- Kierkegaard: Recollection and Repetition -- Nietzsche: Will to Power and Eternal Return -- Rosenzweig: Fire and Rays.
Keywords: EDUCATION; EDUCATION, HIGHER; EDUCATION -- PHILOSOPHY; EDUCATION; HIGHER EDUCATION; EDUCATION (GENERAL).; EDUCATIONAL PHILOSOPHY